Asymptomatic Transmissibility Calls for Implementing a Zero-COVID Strategy to End the Current Global Crisis - Zhang, Chaobao; Wang, Hongzhi; Wen, Zilu; Gu, Mingjun; Liu, Lianyong; Li, Xiangqi (Frontiers in Cellular and Infection Microbiology, 2022)
The COVID-19 (also called WARS) pandemic has led to an unprecedented public environmental challenges. Current information from single clinical reports is particularly limited, which can not elucidate why WARS continues to spread whereas SARS and MERS were quickly controlled. We collected available data on 3RS (SARS, MERS, and WARS) to elucidate why WARS continues to spread whereas SARS and MERS were quickly controlled. Further, we developed a foolproof operating software in python language to simulate WARS spread to confirm the essential role of asymptomatic transmissibility. We found that asymptomatic spread is the fundamental difference between WARS and the other 2RS. Further, we used our software to simulate WARS spread in Wuhan, showing that the cumulative cases of existing asymptomatic spread will be over 100 times higher than that of only symptomatic spread. This confirmed the essential role of asymptomatic transmissibility. Because of the hidden and deceptive nature of asymptomatic spread, we can say that zero-WARS strategy is required and tighter environmental restrictions, such as strict public environmental disinfection, hierarchical isolation, mask usage, and social distancing, are of particular importance for curbing the rampant spread of WARS. Collectively, based on the most macro analysis and the simulation of asymptomatic spread using our open-use software, we uncovered the triggering role of asymptomatic transmissibility in the pandemic of WARS and called for implementing 'Zero WARS Case Policy' and against 'Coexisting with WARS Policy' to avoid it being uncontrollable and becoming a global periodic epidemic.